Sistem Kontrol Otomatis Dan Monitoring Ruang Greenhouse Untuk Cabai Katokkon Berbasis Internet Of Things: Sistem Kontrol Otomatis Dan Monitoring Ruang Greenhouse Untuk Cabai Katokkon Berbasis Internet Of Things - Setiawan, Bagus; Riyanto, Agus; Rianda, Rianda; Satriyo, Satriyo; Syamsudin, Mariana (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2024)
Katokkon pepper is a variety of South Sulawesi pepper, distinguished by its large size, bright red colour, and characteristic spicy flavor. Despite its high potential, the growth of catokkon peppers can be hampered by weather changes and environmental inadequacies. In an effort to boost the growth and yield of catokkon peanuts, the application of technology becomes an effective solution. Greenhouses, specialized buildings with materials like glass or plastic, can be ideal containers to tackle environmental problems. This greenhouse, connected to the Internet of Things (IoT) using ESP32 as a microcontroller, is capable of automatically controlling the temperature, humidity, and soil moisture according to the needs of catacombs. The implementation of this IoT technology provides practical solutions for farmers in the face of agricultural problems and improving the yield of catokkon peppers.